Concepts towards cm-geoid for Nepal GPS to replace conventional leveling using airborne gravity - Manandhar, Niraj; Forsberg, Rene (Journal on Geoinformatics, Nepal, 2008)
This paper gives the concepts of the principles of gravimetric geoid and summarizes the airborne gravity survey and the determination of new national geoid for the height determination by GPS. The paper also deals with the technique of ! tting the computed geoid model with leveling benchmarks and therefore improvement of the geoid will primarily be related to improvements in the vertical datum and GPS data.